1998
DOI: 10.1289/ehp.98106s1289
|View full text |Cite
|
Sign up to set email alerts
|

The role of oxidative stress in chemical carcinogenesis.

Abstract: Oxidative stress results when the balance between the production of reactive oxygen species (ROS) overrides the antioxidant capability of the target cell; oxidative damage from the interaction of reactive oxygen with critical cellular macromolecules may occur. ROS may interact with and modify cellular protein, lipid, and DNA, which results in altered target cell function. The accumulation of oxidative damage has been implicated in both acute and chronic cell injury including possible participation in the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
112
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(113 citation statements)
references
References 29 publications
1
112
0
Order By: Relevance
“…[22][23][24] For example, benzoyl peroxide is known to promote and cause the progression of mouse skin tumorigenesis, 25) and its effects are considered to be due to ROS, e.g., benzoyloxyl radical and hydroxyl radi- All tumors greater than 2 mm in diameter were excised and then fixed with 10% buffered formalin. Histopathological evaluation of tumors induced by DMBA resulted in classification into four lesions as indicated above.…”
Section: Increase In 8-ohdg In Urinementioning
confidence: 99%
“…[22][23][24] For example, benzoyl peroxide is known to promote and cause the progression of mouse skin tumorigenesis, 25) and its effects are considered to be due to ROS, e.g., benzoyloxyl radical and hydroxyl radi- All tumors greater than 2 mm in diameter were excised and then fixed with 10% buffered formalin. Histopathological evaluation of tumors induced by DMBA resulted in classification into four lesions as indicated above.…”
Section: Increase In 8-ohdg In Urinementioning
confidence: 99%
“…Mitochondria are considered as the most important cellular source of ROS and may be susceptible to oxidative damage. ROS can modify cellular protein, lipid, and DNA, which results in altered functions of the cell (Klaunig et al, 1998). It has been reported that ROS, when present at high levels, may play a key role in the mechanisms of initiation and progression of disease such as carcinogenesis (Oberley and Buettner, 1979;Cerutti, 1985;Church et al, 1993;Zhong et al, 1996), and disease associated with aging (Orr and Sohal, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…These highly reactive molecules are generated continuously either by metabolism in ordinary redox reactions, mainly in mitochondria, or through exposure to exogenous stimuli such as infectious and inflammatory agents, pollutants, radiation, or alcohol. 1 Normally, these oxidants are balanced by a synthesis of various defensive proteins. However, if ROS production exceeds the capacity of detoxification systems, principally antioxidant enzymes, oxidative stress is said to occur.…”
mentioning
confidence: 99%